Macma Membership Management System With QR Code - Sufian Yap, Sharin Yap; Ab. Aziz, Ruhaya (International Journal of Advanced Science Computing and Engineering, 2020)
Malaysia Chinese Muslim Associate (MACMA), is an organization that manage the Chinese Muslim community in Malaysia. As one part of MACMA Malaysia, MACMA Negeri Sembilan has the responsibility to manage event and monitor each of their members in the state. However, there are challenges and problems due to the current situation as only two persons involve in the management and administration of the organization. Thus, MACMA membership Management System is developed to manage the organization with more convenient and systematic way. The proposed web based system is equipped with QR Code technology. The QR Code generator was used to record the member attendance in every event organized by MACMA. This system also has plug and play capabilities to ease its implementation. The test result shows that all requirements were fulfilled and the system functioning as expected. Thus, it is hoped that the system can be beneficial and might be implemented to help in the management of other MACMA organization in the other states in Malaysia.